Boron and fluorine co-doped potassium ion battery positive electrode material as well as preparation method and application thereof

By introducing boron and fluorine into the positive electrode material of potassium ion battery, changing the structure and bond energy of the electronic layer, the structural degradation and voltage attenuation of potassium ion battery materials are solved, high cycle stability and rate performance are achieved, and the preparation process is simplified. Reduced costs.

CN119306267AActive Publication Date: 2025-01-14HENAN NORMAL UNIV

Patent Information

Application Number
CN202411836939.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-01-14
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing potassium ion battery positive electrode materials have shortcomings in structural degradation and rapid voltage attenuation, resulting in poor cycle stability and rate performance. The preparation process of existing boron and fluorine co-doped materials is complicated, making it difficult to meet the needs of potassium ion batteries. .

Method used

The preparation method of the positive electrode material of a layered oxide potassium ion battery co-doped boron and fluorine is used to change the structure of the electron layer and introduce B3+ and F- to enhance the TM-O bond, inhibit the Jahn-Teller effect and structural deformation, and provide more Wide ion transport channel, high-temperature calcination process and ball milling process simplify the preparation process.

Benefits of technology

The high cycle stability and high rate performance of the positive electrode material of potassium ion battery are achieved, the structural deformation and irreversible oxidation of oxygen ions are suppressed, the preparation process is simplified, the cost is reduced, and it is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306267A_ABST
    Figure CN119306267A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a boron and fluorine co-doped potassium ion battery positive electrode material, the chemical formula of the boron and fluorine co-doped potassium ion battery positive electrode material is K < 0.5 > Mn < 0.73 > Ni < 0.22 > B < 0.05 > F < 0.05 > O < 1.95 >, bond energy of O-O and TM-O is changed through introduction of boron and fluorine, TM atom spacing is reduced, and interlayer spacing is increased, so that a wider ion transmission channel can be provided, and the service life of the battery is prolonged. And structural deformation is inhibited. In addition, introduction of boron and fluorine inhibits irreversible release of oxygen anions, and side reactions are reduced. The crystal structure of the manganese-based layered metal oxide positive electrode material is synergistically regulated by anions and cations, so that the prepared boron and fluorine co-doped potassium ion battery positive electrode material has good cycling stability and excellent rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of positive electrode materials for potassium ion batteries, and specifically relates to a preparation method and application of a boron and fluorine co-doped positive electrode material for potassium ion batteries. Background Art

[0002] Among various energy storage systems, lithium-ion batteries (LIBs) have become the main power source for consumer electronics and smart wearable devices due to their high energy density, long cycle life, and easy maintenance. However, lithium is scarce and unevenly distributed in the earth's crust, and LIBs alone may not be able to meet future energy demands associated with the rapid growth of the electric vehicle market and stationary storage systems. To address this technical issue, sodium-ion batteries (NIBs) and potassium-ion batteries (KIBs) have become two promising alternatives because they not only have abundant raw material reserves, but also have the same intercalation chemistry as lithium-ion batteries, which is conducive to the design and synthesis of key electrode materials for NIB and KIB applications. In contrast, KIBs have two obvious advantages: First, K / K + The standard redox potential is lower (-2.9 V vs standard hydrogen electrode (SHE)) than Na / Na + (-2.7 V vs SHE), allowing KIB to operate at a higher potential; the other is K + The key challenge in developing KIBs is to explore suitable cathode materials to accommodate large K + ions and understand K + De- / embedding mechanism.

[0003] Compared with other cathode materials, layered oxide compounds have been widely studied due to their advantages of high energy density, simple crystal structure, easy synthesis and commercialization. However, a key problem facing manganese-rich layered cathode materials is structural degradation, which will lead to a low voltage platform and capacity decay during cycling. There are three main reasons for the above results: (1) Mn 3+ The Jahn-Teller effect caused by K accelerates the dissolution of active substances in manganese-based cathode materials, leading to crystal collapse. (2) K + The ionic radius is large (1.38Å), and the cathode material usually undergoes a slow diffusion process and drastic volume change during insertion and extraction, which makes the cathode material prone to structural collapse and leads to rapid capacity decay. (3) The insufficient covalency of the TM−O bond usually leads to excessive oxidation and irreversible lattice oxygen loss, and then TM migration after O2 release due to the lack of coordinated oxygen atoms, resulting in rapid voltage decay.

[0004] The patent document with publication number CN114530601A discloses a method for preparing a boron-doped porous carbon material and its application in potassium ion batteries. The preparation method uses a water-soluble organic acid as a carbon source compound, combines a porogen for boron doping, and prepares a boron-doped porous carbon material with a rich pore structure after freeze drying and high-temperature calcination. When applied to the negative electrode material of potassium ion batteries, it can accelerate the transmission rate of ions and electrons during charging and discharging, and at the same time alleviate the volume change caused by the insertion and removal of potassium ions, effectively improving the electrochemical performance of the battery. However, the boron-doped porous carbon material is used to prepare the negative electrode material of potassium ion batteries, and its rate performance and cycle stability as the positive electrode material of potassium ion batteries still need to be further improved.

[0005] Patent document with announcement number CN117735626B discloses a method and device for preparing a positive electrode material of a sodium ion battery co-doped with boron and fluorine, and adopts a high temperature solid phase method to prepare P2 / O3-Na x TMO2 material, P2 / O3-Na x TMO2 material and a certain amount of LiBF4 are mixed evenly, and the mixed material is calcined to obtain boron and fluorine co-doped P2 / O3-Na x TMB y O 2-z F z Material; F - Introduced into the crystal structure to replace some O 2- , which can greatly improve the electronic conductivity of the material, thereby improving the fast charging ability of the material, and at the same time introduce B into the crystal structure 3+ The structural stability of the material is increased, and the material cycle stability and storage stability are improved, so that the material meets the needs of actual use; the preparation method of the patent document has a wide source of raw materials, low cost, and can be used for large-scale production, which is conducive to the further development of sodium ion batteries. x TMB y O 2-z F z The use of the material as a positive electrode material for potassium ion batteries has not been announced, and the rate performance and cycle stability of potassium ion batteries prepared using it as a positive electrode material cannot be predicted. At the same time, its preparation process adopts a step-by-step solid solution and calcination process, and the preparation process is relatively complicated. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology, and provide a boron-fluorine co-doped potassium ion battery positive electrode material with good cycle stability and excellent rate performance and a preparation method thereof. The advantages of the boron-fluorine co-doped potassium ion battery positive electrode material prepared by the method are: (1) The introduction of boron and fluorine changes the electronic layer structure of the manganese-rich layered oxide, enhances the covalency between the transition metal and oxygen, inhibits the irreversible lattice oxygen loss and Mn 2+ (2) The introduction of boron and fluorine changes the bond energy of OO and TM-O, resulting in a decrease in the distance between TM atoms and an increase in the interlayer distance, thus providing a wider ion transmission channel and inhibiting structural deformation. This synergistic modification of the anion and cation to regulate the crystal structure of the material makes the boron and fluorine co-doped potassium ion battery positive electrode material have the advantages of high cycle stability and high rate performance.

[0007] The present invention adopts the following technical solution to solve the above technical problems, a method for preparing a boron and fluorine co-doped potassium ion battery positive electrode material, and its specific preparation steps are: Step S1: weighing raw materials of manganese dioxide, nickel oxide, anhydrous potassium carbonate, boric acid and potassium fluoride respectively and grinding and mixing them in a mortar to obtain a mixture; Step S2: ball-milling the mixture obtained in step S1 to obtain a mixture powder; Step S3: using a tablet press to tablet the mixture powder obtained in step S2 to obtain a precursor sample; Step S4: calcining the precursor sample obtained in step S3 at high temperature. The high temperature calcination is divided into two steps. The first step is calcining at a temperature of 300-400°C, a heating rate of 2-10°C / min, and a heat preservation time of 1-3h. The second step is calcining at a temperature of 800-900°C, a heating rate of 2-10°C / min, and a heat preservation time of 8-15h. After the heat preservation is completed, the temperature is cooled to room temperature to obtain a boron-fluorine co-doped layered oxide potassium ion battery positive electrode material, whose chemical formula is K 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 .

[0008] Further defined, in step S1, according to K 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95Manganese dioxide, nickel oxide, anhydrous potassium carbonate, boric acid and potassium fluoride are weighed in a stoichiometric ratio, among which K2CO3 needs to be in excess of 3%~10% to compensate for part of the K loss during the sintering process. The weighed raw materials are transferred to a mortar and ground for 5~10 minutes, and then transferred to a ball mill for ball milling.

[0009] It is further defined that the ball milling process in step S2 is to add the mixture obtained in step S1 into a ball milling jar, then add anhydrous ethanol or acetone, and ball mill for 6 to 12 hours at a ball-to-material ratio of (10 to 20) to a mass ratio of 1 and a rotation speed of 400 to 500 r / min.

[0010] It is further defined that the pressure when tabletting using the tablet press in step S3 is set to 10-20 MPa, and the mass of each tablet during tabletting is 0.4-0.6 g.

[0011] It is further defined that the specific process of the two-step sintering in step S4 is: the first step calcination temperature is 350°C, the heating rate is 5°C / min, and the holding time is 2h; the second step calcination temperature is 850°C, the heating rate is 5°C / min, and the holding time is 10h.

[0012] The boron and fluorine co-doped positive electrode material prepared by the above preparation method is used in the preparation of the positive electrode of potassium ion battery.

[0013] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The boron and fluorine co-doped potassium ion battery cathode material prepared by the present invention introduces boron and fluorine anions and cations to synergistically adjust the charge density around oxygen ions, enhance the covalency of TM-O and TM-F, thereby inhibiting the irreversible redox of oxygen ions and the dissolution of transition metals, and reducing the occurrence of side reactions.

[0014] 2. The present invention introduces boron cations to alleviate anisotropic strain and reduce interlayer sliding, thereby inhibiting the occurrence of phase change.

[0015] 3. The present invention introduces boron and fluorine to reduce the distance between TM atoms and increase the interlayer distance, which can provide a wider ion transmission channel and improve K + Diffusion rate and inhibit structural deformation.

[0016] 4. The boron and fluorine co-doped potassium ion battery positive electrode material of the present invention has abundant raw material sources, and the synthesis method is simple, safe and green. It does not require complicated processing procedures and high-end instruments, has relatively low costs, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is boron and fluorine co-doped K in Example 1 0.5 Mn 0.73 Ni0.22 B 0.05 F 0.05 O 1.95 SEM image of the positive electrode material; Figure 2 is boron and fluorine co-doped K in Example 1 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 XRD pattern of positive electrode material; Figure 3 is boron and fluorine co-doped K in Example 1 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 EDS spectrum of cathode material; Figure 4 is boron and fluorine co-doped K in Example 1 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 TEM image of the cathode material; Figure 5 Example 1 boron and fluorine co-doped K 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 The charge and discharge curve diagram of Figure 6 The positive electrode materials prepared in Example 1 and Comparative Examples 1-3 were -1 Cycling performance diagram under current density; Figure 7 The figure is a rate performance diagram of the positive electrode materials prepared in Example 1 and Comparative Examples 1-3 at different current densities. DETAILED DESCRIPTION

[0018] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention. Example 1

[0019] Boron and fluorine co-doped K 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95Preparation of positive electrode materials: (1) According to K 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 Manganese dioxide, nickel oxide, anhydrous potassium carbonate, boric acid and potassium fluoride were weighed in a stoichiometric ratio, wherein K2CO3 was used in an excess of 5% to compensate for the partial K loss during the sintering process, and the weighed raw materials were transferred to a mortar and ground for 5 minutes to obtain a mixture; (2) Pour the mixture obtained in step (1) into a ball mill, add zirconium oxide balls in a ball-to-material mass ratio of 10:1, and add anhydrous ethanol with a dropper. Set the ball mill speed to 500 r / min and the ball milling time to 6 h. Place the ball-milled sample in an oven and dry it at 80° C. for 2 h to obtain a uniformly mixed mixture powder. (3) Pressing the mixture powder obtained in step (2) into tablets on a tablet press at a pressure of 10 MPa to obtain a precursor sample, wherein the mass of each tablet is 0.5 g; (4) The precursor sample prepared in step (3) was transferred to a porcelain boat and heated in a muffle furnace at 5 °C min −1 The temperature was raised to 350 °C at a rate of 2 h and then heated at 5 °C min −1 The temperature was raised to 850℃ at a heating rate of 10 hours, and then naturally cooled to room temperature after the heating, and then crushed to obtain boron and fluorine co-doped K 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 Positive electrode material, abbreviated as KMNBOF.

[0020] Comparative Example 1 K doped with single non-metallic boron 0.5 Mn 0.73 Ni 0.22 B 0.05 Preparation of O2 cathode materials: (1) According to K 0.5 Mn 0.73 Ni 0.22 B 0.05 Manganese dioxide, nickel oxide, anhydrous potassium carbonate and boric acid were weighed in a stoichiometric ratio of O2, wherein K2CO3 was used in an excess of 5% to compensate for the partial K loss during the sintering process. The weighed raw materials were transferred to a mortar and ground for 5 min to obtain a mixture; (2) Pour the mixture obtained in step (1) into a ball mill, add zirconium oxide balls in a ball-to-material mass ratio of 10:1, and add anhydrous ethanol with a dropper. Set the ball mill speed to 500 r / min and the ball milling time to 6 h. Place the ball-milled sample in an oven and bake at 80° C. for 2 h to obtain a uniformly mixed mixture powder; (3) Pressing the mixture powder obtained in step (2) into tablets on a tablet press at a pressure of 10 MPa to obtain a precursor sample, wherein the mass of each tablet is 0.5 g; (4) The precursor sample obtained in step (3) was transferred to a porcelain boat and heated in a muffle furnace at 5 °C min −1 The temperature was raised to 350 °C at a rate of 2 h and then heated at 5 °C min −1 The temperature was raised to 950°C at a heating rate of 100 °C and kept for 10 h. After the temperature was naturally cooled to room temperature, the layered oxide K doped with a single non-metallic boron was obtained by pulverization. 0.5 Mn 0.73 Ni 0.22 B 0.05 O2 positive electrode material, abbreviated as KMNBO.

[0021] Comparative Example 2 K doped with single non-metallic fluorine 0.5 Mn 0.78 Ni 0.22 O 1.95 F 0.05 Preparation of positive electrode materials: (1) According to K 0.5 Mn 0.78 Ni 0.22 O 1.95 F 0.05 Manganese dioxide, nickel oxide, anhydrous potassium carbonate and potassium fluoride are weighed in a stoichiometric ratio, wherein K2CO3 needs to be in excess of 5% to compensate for some K loss during sintering, and the weighed raw materials are transferred to a mortar and ground for 5 minutes to obtain a mixture; (2) The mixture obtained in step (1) was poured into a ball mill, zirconium oxide balls were added in a ball-to-material mass ratio of 10:1, and anhydrous ethanol was added using a dropper. The ball mill speed was set to 500 r / min, and the ball milling time was set to 6 h. The ball-milled sample was placed in an oven and dried at 80° C. for 2 h to obtain a uniformly mixed mixture powder.

[0022] (3) Pressing the mixture powder obtained in step (2) into tablets on a tablet press at a pressure of 10 MPa to obtain a precursor sample, wherein the mass of each tablet is 0.5 g; (4) Transfer the precursor sample obtained in step (3) to a porcelain boat and heat it in a muffle furnace at 5°C min −1The temperature was raised to 350 °C at a rate of 2 h and then heated at 5 °C min −1 The temperature was raised to 850℃ at a heating rate and kept for 10h. After the temperature was naturally cooled to room temperature, it was crushed to obtain K doped with single non-metallic fluorine. 0.5 Mn 0.78 Ni 0.22 O 1.95 F 0.05 Positive electrode material, abbreviated as KMNOF.

[0023] Comparative Example 3 K without boron or fluorine doping 0.5 Mn 0.78 Ni 0.22 Preparation of O2 cathode materials: (1) According to K 0.5 Mn 0.78 Ni 0.22 Manganese dioxide, nickel oxide and anhydrous potassium carbonate were weighed in a stoichiometric ratio of O2, wherein K2CO3 was used in an excess of 5% to compensate for the partial K loss during the sintering process. The weighed raw materials were transferred to a mortar and ground for 5 min to obtain a mixture; (2) Pour the mixture obtained in step (1) into a ball mill, add zirconium oxide balls in a ball-to-material mass ratio of 10:1, and add anhydrous ethanol with a dropper. Set the ball mill speed to 500 r / min and the ball milling time to 6 h. Place the ball-milled sample in an oven and dry it at 80° C. for 2 h to obtain a uniformly mixed mixture powder; (3) The mixture powder obtained in step (2) was pressed into tablets on a tablet press at a pressure of 10 MPa to obtain a precursor sample, and the mass of each tablet was 0.5 g; (4) The precursor sample obtained in step (3) was transferred to a porcelain boat and heated in a muffle furnace at 5 °C min −1 The temperature was raised to 350 °C at a rate of 2 h and then heated at 5 °C min −1 The temperature was raised to 850℃ at a heating rate and kept for 10h. After the temperature was naturally cooled to room temperature, it was crushed to obtain K without boron and fluorine doping. 0.5 Mn 0.78 Ni 0.22 O2 positive electrode material, abbreviated as KMNO.

[0024] Characterization of materials: Figure 1 Boron and fluorine co-doped K 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 SEM image of the positive electrode material. Figure 1The material is shown to be an irregular block structure; Figure 2 Boron and fluorine co-doped K 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 The XRD pattern of the positive electrode material shows that the material is a layered metal oxide of P2 phase with a space group of P63 / mmc ; Figure 3 Boron and fluorine co-doped K 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 The EDS spectrum of the positive electrode material shows the presence of K, Mn, Ni, B, F, and O elements, and their contents are basically consistent with the chemical formula. Figure 4 Boron and fluorine co-doped K 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 TEM image of the positive electrode material. It can be seen from the image that the positive electrode material shows high-resolution lattice fringes with a spacing of 0.64nm, corresponding to the (002) plane of the p2 type structure.

[0025] The positive electrode materials prepared in Example 1 and Comparative Examples 1-3 were subjected to electrochemical performance tests, and the results are shown in Table 1.

[0026] Electrochemical performance test: Using N-methylpyrrolidone as solvent, the prepared cathode material was ground and mixed with super-p and polyvinylidene fluoride at a mass ratio of 70:20:10. The obtained uniform slurry was applied on Al foil and transferred to a vacuum drying oven and dried at 80°C for 12h. 0.8mol L −1 KPF6 diethyl carbonate (DEC) solution was used as the electrolyte of potassium ion battery, glass fiber and metallic potassium were used as the separator and counter electrode of potassium ion battery respectively. CR2032 battery was used for the test of electrochemical performance. The battery was assembled in a glove box filled with argon atmosphere, and the water and oxygen concentrations were less than 0.1ppm. The constant current charge and discharge test of the battery was carried out at room temperature using Blue Power CT2001A multi-channel battery test system at 1.5-4.0V (vs. K + / K) fixed voltage range.

[0027] Figure 5 Boron and fluorine co-doped K prepared in Example 1 0.5 Mn 0.73 Ni 0.22 B 0.05 F0.05 O 1.95 The charge and discharge curve of the positive electrode material shows that the boron and fluorine co-doped K prepared in Example 1 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 The positive electrode material has good rate performance.

[0028] Figure 6 The potassium ion battery assembled with the positive electrode materials prepared in Example 1 and Comparative Examples 1-3 was subjected to 20 mA g −1 The cycling performance diagram under current density shows that the boron and fluorine co-doped K prepared in Example 1 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 The capacity retention rate of the positive electrode material after 100 cycles is 86.3%, which is much higher than that of the single boron-doped K prepared in Comparative Examples 1-3. 0.5 Mn 0.73 Ni 0.22 B 0.05 O2 cathode material, single fluorine-doped K 0.5 Mn 0.78 Ni 0.22 O 1.95 F 0.05 Positive electrode materials and undoped ion K 0.5 Mn 0.78 Ni 0.22 O2 positive electrode material. Figure 7 The rate performance of the positive electrode materials prepared in Example 1 and Comparative Examples 1-3 at different current densities is shown in the figure. Even at 300 mA g −1 At a high current density of 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 The positive electrode material capacity can still reach 70mAh g −1 capacity.

[0029] Table 1 Test results sample <![CDATA[Initial discharge specific capacity (20 mA g −1 ).]]> <![CDATA[Capacity retention rate after 100 cycles / % (20 mA g −1 ).]]> <![CDATA[300mA g −1 Specific capacity at rate (mAh g −1 )]]> Example 1 102 86.3 70 Comparative Example 1 93 76 53.5 Comparative Example 2 91 66.4 36 Comparative Example 3 83 49.4 21 It can be seen from the results in Table 1 that, compared with the positive electrode materials prepared in Comparative Examples 1-3, the anion-cation co-doped potassium ion battery positive electrode material of Example 1 has the best first discharge specific capacity, cycle stability and rate performance. This is mainly because the boron and fluorine co-doped potassium ion battery positive electrode material forms enhanced TM-O and TM-F bonds after anion-cation doping, which narrows the TMO2 layer and expands the interlayer spacing. Therefore, KMNBOF can provide a wider ion transmission channel, which is beneficial to K + In addition, due to the existence of Mn-F bonds, the diffusion of Mn 2+ dissolution into the electrolyte, promoting the 2+ and Mn 4+ The reversible transformation between , thus inhibiting the Jahn-Teller effect; and B 3+ After entering the TM layer, it helps to reduce the effective coordination of O atoms, thereby inhibiting the redox of oxygen anions. This mechanism of coordinated modification and regulation of the crystal structure of the material by anions and cations will expand the distance between potassium layers, which is beneficial to the transport of potassium ions and reduce the loss of lattice oxygen, which can not only improve the rate performance but also improve the structural stability.

[0030] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a boron and fluorine co-doped potassium ion battery positive electrode material, characterized in that The specific preparation steps are: Step S1: weighing raw materials of manganese dioxide, nickel oxide, anhydrous potassium carbonate, boric acid and potassium fluoride respectively and grinding and mixing them in a mortar to obtain a mixture; Step S2: ball-milling the mixture obtained in step S1 to obtain a mixture powder; Step S3: using a tablet press to tablet the mixture powder obtained in step S2 to obtain a precursor sample; Step S4: calcining the precursor sample obtained in step S3 at high temperature. The high temperature calcination is divided into two steps. The first step is calcining at a temperature of 300-400°C, a heating rate of 2-10°C / min, and a heat preservation time of 1-3h. The second step is calcining at a temperature of 800-900°C, a heating rate of 2-10°C / min, and a heat preservation time of 8-15h. After the heat preservation is completed, the temperature is cooled to room temperature to obtain a boron-fluorine co-doped layered oxide potassium ion battery positive electrode material, whose chemical formula is K 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 .

2. The method for preparing the boron and fluorine co-doped potassium ion battery positive electrode material according to claim 1, characterized in that: In step S1, according to K 0.5 Mn 0.73 Ni 0.22 B 0.05 F 0.05 O 1.95 Manganese dioxide, nickel oxide, anhydrous potassium carbonate, boric acid and potassium fluoride are weighed in a stoichiometric ratio, among which K2CO3 needs to be in excess of 3%~10% to compensate for part of the K loss during the sintering process. The weighed raw materials are transferred to a mortar and ground for 5~10 minutes, and then transferred to a ball mill for ball milling.

3. The method for preparing the boron and fluorine co-doped potassium ion battery positive electrode material according to claim 1, characterized in that: The ball milling process in step S2 is to add the mixture obtained in step S1 into a ball milling jar, then add anhydrous ethanol or acetone, and ball mill for 6 to 12 hours at a ball-to-material ratio of (10 to 20) to a mass ratio of 400 to 500 r / min.

4. The method for preparing the boron and fluorine co-doped potassium ion battery positive electrode material according to claim 1, characterized in that: The pressure during tableting using the tablet press in step S3 is set to 10-20 MPa, and the mass of each tablet during tableting is 0.4-0.6 g.

5. The method for preparing the boron and fluorine co-doped potassium ion battery positive electrode material according to claim 1, characterized in that The specific process of the two-step sintering in step S4 is as follows: the first step calcination temperature is 350°C, the heating rate is 5°C / min, and the holding time is 2h; the second step calcination temperature is 850°C, the heating rate is 5°C / min, and the holding time is 10h.

6. Use of the boron and fluorine co-doped positive electrode material prepared according to the method according to any one of claims 1 to 5 in the preparation of a positive electrode for a potassium ion battery.

Citation Information

Patent Citations

  • Potassium ion battery positive electrode material and preparation method thereof

    CN108417825A

  • Potassium ion battery cathode material based on Ni / Mn binary oxide and preparation method thereof

    CN108615874A

  • Preparation method and application of potassium ion battery positive electrode material

    CN109713295A

  • Method for preparing novel potassium ion battery positive electrode material through two-step potassium supplementation

    CN113336277A

  • Surface coating modified nickel-cobalt-manganese ternary material as well as preparation method and application thereof

    CN114497494A

Cited By

  • In-situ boron-fluorine co-doped ternary precursor and preparation method and application thereof

    CN121494001A

  • In-situ boron-fluorine co-doped ternary precursor, preparation method and application thereof

    CN121494001B